Outpatient Operative Management of Pediatric Supracondylar Humerus Fractures: An Analysis of Frequency, Complications, and Cost From 2009 to 2018. Issue 1 (4th January 2022) - Modest, Jacob M.; Brodeur, Peter G.; Lemme, Nicholas J.; Testa, Edward J.; Gil, Joseph A.; Cruz, Aristides I.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In an effort to increase the value of health care in the United States, there has been increased focus on shifting certain procedures to an outpatient setting. While pediatric supracondylar humerus fractures (SCHFs) have traditionally been treated in an inpatient setting, recent studies have investigated the safety and efficiency of outpatient surgery for these injuries. This retrospective study aims to examine ongoing trends of outpatient surgical care for SCHFs, examine the safety and complication rates of these procedures, and investigate the potential cost-savings from this shift in care. Methods: Pediatric patients less than 13 years old who underwent surgery for closed SCHF from 2009 to 2018 were identified using International Classification of Diseases-9/10 Clinical Modification and Procedural Classification System codes in the New York Statewide Planning and Research Cooperative System (SPARCS) database. Linear regression was used to assess the shift in proportion of outpatient surgical management of these injuries over time. Multivariable Cox proportional hazards regression was used to compare return to emergency department (ED) visit, readmission, reoperation, and other adverse events. A 2-sample t test was performed on the average charge amount per claim for inpatient versus outpatient surgery. Results: A total of 8488 patients were included in the analysis showing there was a statistically significant shift towards outpatient management between 2009 (23% outpatient) and 2018 (59% outpatient) ( P <0.0001). Relative to inpatient surgical management, outpatient surgical management had lower rates of return ED visits at 1 month (hazard ratio: 0.744, P =0.048). All other adverse events compared across inpatient and outpatient surgical management were not significantly different. The median amount billed per claim for inpatient surgeries was significantly higher than for outpatient surgeries (16, 097 vs. 9, 752, P <0.0001). White race, female sex, and weekday ED visit were associated with increased rate of outpatient management. Conclusions: This study demonstrates the trend of increasing outpatient surgical management of pediatric SCHF from 2009 to 2018. The increased rate of outpatient management has not been associated with elevated complication rates but is associated with significantly reduced health care charges. Level of Evidence: Level III—retrospective cohort.